A fórmula de aproximação de Baouendi -Treves - Liboni Filho, Paulo Antonio (2009)
Let be a N-dimensional smooth manifold. Consider a locally integrable structure L of CT with fiber dimension 1 ≤ n < N and set m = N − n. We say that L is locally integrable if, for every p ∈ , there is a neiborhood Up and m smooth functions Zj : U −→ C, 1 ≤ j ≤ m such that 1. Zj is anihilated by every local section of L; 2. dZ1(p) ∧ . . . ∧ dZm(p) 6= 0. The main result in this text is the Baouendi-Treves Approximation Theorem, that states that every distribution solution u of the sections of L is locally the limit of a sequence of smooth solutions of the form Pk ◦ Z, where Z = (Z1, . . . ,Zm) and Pk is a m-variable polynomial.